2023
DOI: 10.1111/nph.18730
|View full text |Cite
|
Sign up to set email alerts
|

A high‐confidence Physcomitrium patens plasmodesmata proteome by iterative scoring and validation reveals diversification of cell wall proteins during evolution

Abstract: Summary Plasmodesmata (PD) facilitate movement of molecules between plant cells. Regulation of this movement is still not understood. Plasmodesmata are hard to study, being deeply embedded within cell walls and incorporating several membrane types. Thus, structure and protein composition of PD remain enigmatic. Previous studies of PD protein composition identified protein lists with few validations, making functional conclusions difficult. We developed a PD scoring approach in iteration with large‐scale syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…While this might arise from our fractionation methods being suboptimal for their extraction, or from usage of non-quantitative MS methods, we found that if we reduced the stringency of protein identification in both our Arabidopsis leaf and moss plasmodesmal fractions, allowing an identification probability of >50% threshold for peptide and protein identification and a minimum of one sample, we identify an additional 12 orthogroups present in at least four of five proteomes, one of which represents callose synthases ( Supplementary Tables S2 , S3 , S7 ). This low stringency analysis also reveals orthogroups containing heavy metal-associated isoprenylated proteins (HIPPs), which have been localized to plasmodesmata in Arabidopsis ( Guo et al , 2021 ) and N. benthamiana ( Cowan et al , 2018 ), and xyloglucan endotransglucosylase/hydrolase proteins, which have been confirmed as plasmodesmal proteins in a concomitant proteomic study ( Gombos et al , 2023 ). In essence, by requiring the identification of a protein in multiple independent proteomes, we are increasing the a priori likelihood of protein identification within a sample.…”
Section: Discussionmentioning
confidence: 86%
“…While this might arise from our fractionation methods being suboptimal for their extraction, or from usage of non-quantitative MS methods, we found that if we reduced the stringency of protein identification in both our Arabidopsis leaf and moss plasmodesmal fractions, allowing an identification probability of >50% threshold for peptide and protein identification and a minimum of one sample, we identify an additional 12 orthogroups present in at least four of five proteomes, one of which represents callose synthases ( Supplementary Tables S2 , S3 , S7 ). This low stringency analysis also reveals orthogroups containing heavy metal-associated isoprenylated proteins (HIPPs), which have been localized to plasmodesmata in Arabidopsis ( Guo et al , 2021 ) and N. benthamiana ( Cowan et al , 2018 ), and xyloglucan endotransglucosylase/hydrolase proteins, which have been confirmed as plasmodesmal proteins in a concomitant proteomic study ( Gombos et al , 2023 ). In essence, by requiring the identification of a protein in multiple independent proteomes, we are increasing the a priori likelihood of protein identification within a sample.…”
Section: Discussionmentioning
confidence: 86%
“…They consist of a C-terminal ER-anchor and three to four C2 lipid binding domains. In Arabidopsis, the MCTP family comprises 16 members, among which MCTP3, MCTP4, and MCTP6 were identified in plasmodesmata fractions in a systematic manner (Fernandez-Calvino et al, 2011; Kraner et al, 2017; Brault et al, 2019; Kirk et al, 2022; Miras et al, 2022a; Gombos et al, 2023; Johnston et al, 2023). Given that nearly all plant cells are interconnected by these communication bridges, it is anticipated that a primary component would be widely expressed and consistently associated with plasmodesmata, irrespective of tissue type or developmental stage.…”
Section: Resultsmentioning
confidence: 99%
“…This different function might be related to tissue localization according to proteome in Arabidopsis and Physcomitrium patens . PsEXO1 was localized in plasmodesmata of P. patens and divided into Clade III of the phylogenetic tree and Clade III also contained AtEXO, AtEXL1, and AtEXL2 from Arabidopsis [ 23 ]. AtEXL3, AtEXL5, and AtEXL7 were divided into Clade II [ 23 ] and CsEXL3 was a homologous gene of AtEXL3 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PsEXO1 was localized in plasmodesmata of P. patens and divided into Clade III of the phylogenetic tree and Clade III also contained AtEXO, AtEXL1, and AtEXL2 from Arabidopsis [ 23 ]. AtEXL3, AtEXL5, and AtEXL7 were divided into Clade II [ 23 ] and CsEXL3 was a homologous gene of AtEXL3 ( Fig. S7 , see online supplementary material).…”
Section: Discussionmentioning
confidence: 99%